Backbone’s and Joints’ Problems – Nature and Solutions (Global Journal of Medical Research, 2023)
Based on my research I explain in this article that the psychological stress is not the primary factor that causes the backbone s and joints pain in elderly The primary cause is their congested body which had never been flushed When the congested body is influenced by negative emotions stress or just negative thinking which decrease the body energy and farther slowdown the processes in it the level of pain goes up To decease the backbone s and joints pain in the elderly periodic cleansing of the body is recommended and exercises with extension of the backbone 1 by hanging on the arms and letting the body be pulled down by the gravitational forces and 2 exercises of crawling on the arms and toes called crocodile crawling which extend the backbone and free it from the vertical pressure of walking on two legs
Keywords: backbone pain; joints’ pain; periodic cleansing recommended